Ralph Waldo Emerson’s Literary Works: A Reflection of Hindu Philosophy - Neupane, Khagendra (Cognition, 2021)
The researcher explores how Emerson blends the East and the West in his literary works. In order to observe the influence of Eastern philosophy in his works, some of his representative literary texts like The Poet, The Over-Soul, Nature and Illusion are analyzed in detail. Emerson embodies the notion of Karma, Over-Soul and Pantheism in his texts. He browses through the Vedas, the Gita and the Upanishads, Eastern philosophical texts and ultimately encompasses their essence in his works. He also advocates the notion of Transcendentalism, going beyond the nature, together with Hinduism.